2017
DOI: 10.1159/000480539
|View full text |Cite
|
Sign up to set email alerts
|

Naltrexone in the Treatment of Broadly Defined Behavioral Addictions: A Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction: Broadly defined behavioral addiction is a conceptual framework including behaviors characterized by loss of control and continuation despite significant negative consequences. Broadly defined behavioral addictions share many similarities with substance use disorders. As naltrexone is one of the most studied treatment for substance use disorders, we conducted a meta-analysis of randomized placebo-controlled trials (RCT) assessing the effectiveness of naltrexone in the treatment of broadly defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 29 publications
2
19
0
3
Order By: Relevance
“…For example, naltrexone reverses the increased delay discounting induced by morphine administration in rats (Kieres et al, 2004). In humans, it enhances inhibitory control and has variable effects on impulsive choice that depend on individual locus of control scores (Altamirano et al, 2011, Mitchell et al, 2007., and several clinical studies have found naltrexone effective in treating impulse control disorders (Kim, 1998, Papay et al, 2014, Schreiber et al, 2011, although its effectiveness is not universal (Mouaffak et al, 2017, Toneatto et al, 2009. However, conflicting data from alcohol-dependent patients found naltrexone had no effect on several measures of impulsivity (Zorlu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, naltrexone reverses the increased delay discounting induced by morphine administration in rats (Kieres et al, 2004). In humans, it enhances inhibitory control and has variable effects on impulsive choice that depend on individual locus of control scores (Altamirano et al, 2011, Mitchell et al, 2007., and several clinical studies have found naltrexone effective in treating impulse control disorders (Kim, 1998, Papay et al, 2014, Schreiber et al, 2011, although its effectiveness is not universal (Mouaffak et al, 2017, Toneatto et al, 2009. However, conflicting data from alcohol-dependent patients found naltrexone had no effect on several measures of impulsivity (Zorlu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The difference between reported outcomes and a small number of studies has made it difficult to present results in a metaanalysis. However, to illustrate the effect of the drug in each study, the total effect size of each study for repeated measurements at different time intervals was calculated and reported using a fixed effect model [51].…”
Section: Resultsmentioning
confidence: 99%
“…Similarities between kleptomania and OCD or SAD also exist concerning treatment options that have been proven effective at least at case-report level: selective serotonin reuptake inhibitors (SSRIs) are regarded effective in OCD as well as in kleptomania (Lepkifker et al, 1999). Opioid antagonists such as naltrexone have been used in SAD and kleptomania (Grant et al, 2009, Grant et al, 2014Mouaffak et al, 2017). Other treatment forms of kleptomania include cognitive behavioural therapy (CBT) (Christianini et al, 2015;Rudel et al, 2009) with covert sensitization and systematic desensitization.…”
Section: Introductionmentioning
confidence: 99%